Impact on clinical outcomes from transcatheter closure of the Fontan fenestration: A systematic review and meta-analysis - Greenleaf, Christopher E.; Lim, Zhia Ning; Li, Wen; LaPar, Damien J.; Salazar, Jorge D.; Corno, Antonio F. (Frontiers in Pediatrics, 2022)
Background. Meta-analysis on late outcomes of fenestration in Fontan procedure. Methods. Cochrane, Embase, MEDLINE, and Open-Grey were searched. Non-comparative series and case reports were excluded. Parameters such as changes in oxygen saturation, cavo-pulmonary pressure, maximum heart rate during exercise, exercise duration, and oxygen saturation after fenestration closure were pooled and statistical analysis performed. Results. Among 922 publications, 44 retrospective observational studies were included, including those characterizing late catheter closure of fenestration (31 articles) and interventional reopening/stenting or creation of fenestration (13 articles). Interventional catheter closure of fenestration. 877 patients (46.3%) received interventional catheter closure at mean interval of 27.4 months (2 months-17.2 years). After fenestration closure there was a significant increase in arterial oxygen saturation (7.9%, P<0.01) and exercise duration (1.7 minutes, P<0.01). However, there was also associated increase in mean cavo-pulmonary pressure (1.4mmHg, P<0.01). Creation or enlargement/stenting of fenestration. Out of 1,587 patients aged between 2 months and 14 years, 32.5% had fenestration during surgery, 13.6% received interventional creation of fenestration, and 9.3% received dilation/stenting of existing fenestration. 24 patients had fenestration created due to protein-losing enteropathy. None of the studies reported odds ratios or mean differences in any outcomes, thus meta-analysis could not be performed. Conclusions. Late closure of a Fontan fenestration improves resting oxygen saturation, exercise oxygen saturation, and exercise duration. Concrete conclusions remain guarded regarding the management of creation/enlargement of Fontan fenestrations. The lack of comparative data suggests the need for better, prospective trials looking at role of fenestration in management of late Fontan failure.